Hydrochemistry of Cachoeira River (Bahia State, Brazil) Hidroquímica do Rio Cachoeira (Bahia, Brasil) - Maria Zita Tabosa Pinheiro de Queiroz Lima Lucio (Acta Limnologica Brasiliensia, 2012)
AIM: The aim of this study is to evaluate the spatial-temporal changes of chemical elements in the surface waters of the Cachoeira River in order to evaluate the impacts of anthropogenic activities in water quality; METHODS: Samples were collected monthly between August 2008 and August 2009 at six collection points along the river. The abiotic parameters dissolved oxygen, pH, electrical conductivity and temperature were performed in the field using portable digital meters; concentration of ions nitrite (NO2-), nitrate (NO3-), ammonia (NH4+), phosphate (PO4-), sodium (Na+), calcium (Ca+2), potassium (K+), chloride (Cl-), magnesium (Mg+2), sulfate (SO4-2) were determined by ion chromatography and bicarbonate (HCO3-) was calculated by a model of ionic associations originated from alkalinity values; RESULTS: The spatial variations showed that anthropogenic activities and land use changes (cocoa crops and pasture) appear to be the major factors influencing the distribution of nutrients in the Cachoeira River; however, lithology seems to be the factor influencing the major ions; CONCLUSIONS: Variations in ion concentrations were directly related to drought and rainy periods, the geological formation, and the various land uses. The lack of treatment of domestic wastes and their incorrect disposal in water bodies has significantly contributed to the aggravation of environmental problems and consequently the health of the population. OBJETIVO: O objetivo do presente estudo foi avaliar as variações espaço temporais da química das águas superficiais do Rio Cachoeira a fim de estabelecer os impactos das atividades antropogênicas na qualidade da água; MÉTODOS: As coletas foram realizadas mensalmente entre agosto de 2008 e agosto de 2009 em seis pontos de coleta ao longo do rio. Os parâmetros abióticos oxigênio dissolvido, pH, condutividade elétrica e temperatura foram determinados através de medidores portáteis no campo; a concentração dos íons nitrito (NO2-), nitrato (NO3-), amônia (NH4+), fosfato (PO4-), sódio (Na+), cálcio (Ca+2), potássio (K+), cloreto (Cl-), magnésio (Mg+2), sulfato (SO4-2) através da cromatografia iônica e o bicarbonato (HCO3-) através da alcalinidade; RESULTADOS: Os resultados referentes a variação espacial no Rio Cachoeira demonstraram que as atividades antropogênicas e os diferentes cultivos ao longo da bacia (cultivo de cacau e pastagem) são os principais fatores que influenciam na distribuição dos nutrientes (N e P). No entanto, a litologia parece ser o principal responsável pelas concentrações dos íons maiores, não havendo diferenças entre os pontos de coleta; CONCLUSÕES: As variações das concentrações dos íons foram diretamente relacionadas aos períodos mais secos e mais chuvosos, a formação geológica e aos diversos usos da terra. A ausência do tratamento de resíduos domésticos e seu despejo impróprio nos corpos de água têm contribuído para o agravamento dos problemas ambientais e consequentemente à saúde da população.